Laboratory evaluation of the efficacy of Liastene application in complex therapy of multiresistant pulmonary tuberculosis - I.L. Platonova; M.I. Sakhelashvili; G.D. Shtybel; O.I. Sakhelashvili-Bil (Civic Union "Communicable Diseases Intensive Care Association", 2021)
OBJECTIVE. Evaluating according to laboratory tests the effectiveness of Liasten in the treatment of patients with multidrug-resistant pulmonary tuberculosis (MDR-TB). MATERIALS AND METHODS. Evaluation of the effectiveness of etiotropic and etiopathogenetic therapy in 57 patients with MDR-TB was performed. According to the treatment schemes, patients were divided into groups. The control group (n=22) received individualized antimycobacterial therapy (AMBT) regimens. The experimental group (n=35) received AMBT in combination with Liasten. Evaluation of the effectiveness of treatment regimens was performed on the basis of indicators of general clinical blood tests, immunological and bacteriological studies. RESULTS AND DISCUSSION. In patients of the experimental group, compared with the control in 1.5 times more often found positive changes in the hemogram of blood and ESR (p<0.05-0.001), the establishment of a dynamic balance between the pools of lymphocyte cells CD4+ and СD8+ (immunoregulatory index, p<0.05), an increase in the number of phagocytosis active cells (phagocytic index, p<0.05), the content of cationic lysosomal proteins of granulocyte leukocytes (p<0.05), a 1.4-fold decrease in the cytochemical coefficient of neutrophils (p<0.05), the number of proliferated under the action of PPD-L lymphocytes (p<0.05), normalization of phagocytic counts and total redox activity of neutrophils (p<0.05), increase in frequency and reduction of anesthesia was stated. CONCLUSIONS. Restoration of the body's immune status, blood hemogram, increase in frequency and reduction of the time of decontamination were more active and occurred 1.5 times more often in patients receiving a complex combination of AMBT with Liasten.